Surface Modification of Natural Rubber by Sulfur hexafluoride (SF6) Plasma Treatment: A New Approach to Improve Mechanical and Hydrophobic Properties - Cabrera, F.C.; Dognani, G.; Santos, R.J. dos; Agostini, D.L.S.; Cruz, N.C.; Job, A.E. (Journal of Coating Science and Technology, 2016)
Plasma treatments have faced growing interest as important strategy to modify the hydrophobic/hydrophilic characteristics of materials. However, challenges related to the plasma modification of polymers are the improvement of the chemical resistance without decreasing the mechanical resistance. In this letter, we present for the first time a plasma treatment, using Sulfur hexafluoride (SF6), analogous to vulcanization process, of natural rubber surface, which resulted in a chemical and tension resistance improvements. The natural rubber membranes were coated with glow discharge plasmas generated in sulfur hexafluoride (SF6) atmospheres at a total pressure of 160 mTorr and applying 70 W of radiofrequency. Plasma treatment increases the contact angles from 64° to 125° i.e. leading to a hydrophobic surface. The tension at rupture increased from 3.7 to 6.1 MPa compared to natural rubber without plasma treatment demonstrated by stress-strain investigation. These results provide a fast alternative approach to improve mechanical and chemical properties of rubber-based products.